ON THE METHOD OF COMPARING STRUCTURES BASED ON THE DATA IN THE CONTINGENCY TABLES - Polko, Dominika (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
Comparison of populations is one of the most important problems in statistics. The most common comparisons apply to two populations, but comparisons of k populations, where k > 2 are also carried out. Parametric methods allow to compare the means, variances or proportions. The non-parametric methods allow to compare the distributions of two or more populations. The problem of comparison structures based on data in contingency tables is analyzed in the paper. The permutation tests were applied in the multivariate nominal data structure comparison.